2023
DOI: 10.3389/fmicb.2023.1066805
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the diversity and structure of the rhizosphere microbial community between the straight and twisted trunk types of Pinus yunnanensis

Abstract: BackgroundPinus yunnanensis is a major silvicultural species in Southwest China. Currently, large areas of twisted-trunk Pinus yunnanensis stands severely restrict its productivity. Different categories of rhizosphere microbes evolve alongside plants and environments and play an important role in the growth and ecological fitness of their host plant. However, the diversity and structure of the rhizosphere microbial communities between P. yunnanensis with two different trunk types—straight and twisted—remain un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 128 publications
1
2
0
Order By: Relevance
“…Soil pH, AK, TN, TP, and TK have also been found to be important factors influencing the fungal communities associated with the rhizosphere soil surrounding wild and reintroduced M. sinica individuals [35]. Moreover, available K was found to be correlated with different fungal communities (p = 0.01) in the soils of twisted and straight-trunk individuals of P. yunnanensis [36]. Our results are therefore similar to those of previous studies.…”
Section: Relationships Between Fungal Community and Soil Physicochemi...supporting
confidence: 90%
See 1 more Smart Citation
“…Soil pH, AK, TN, TP, and TK have also been found to be important factors influencing the fungal communities associated with the rhizosphere soil surrounding wild and reintroduced M. sinica individuals [35]. Moreover, available K was found to be correlated with different fungal communities (p = 0.01) in the soils of twisted and straight-trunk individuals of P. yunnanensis [36]. Our results are therefore similar to those of previous studies.…”
Section: Relationships Between Fungal Community and Soil Physicochemi...supporting
confidence: 90%
“…Previous research compared the diversity and structure of the rhizosphere fungal community between the straight and twisted trunk types of Pinus yunnanensis. The fungal communities' composition in the rhizosphere of straight and twisted bark varieties included Basidiomycota (72.96 and 68.35%, respectively) and Ascomycota (26.12 and 29.76%, respectively), with an overall relative abundance of more than 98% in both groups [36]. Many fungi convert dead organic matter into biomass, carbon dioxide, and organic acids, can effectively decompose organic matter and soil components, and thereby, regulate the balance of carbon and nutrients [7].…”
Section: Community Structure Of P Squamata Rhizosphere Fungimentioning
confidence: 99%
“…Its significance lies in its ability to act as a substrate for DNA synthesis enzymes, contributing to the maintenance of genetic stability [65]. In addition, the study found that the rhizosphere microbial community between the straight and twisted trunk types of P. yunnanensis was different [66]. In summary, the differences in microbes may affect the growth of P. yunnanensis based on plant-microbe interactions.…”
Section: Discussionmentioning
confidence: 92%